Late Quaternary climatic fluctuations and the depositional history of the Bengal basin - Monsur, M. H.; Chowdhury, M. M. M. (Journal of Nepal Geological Society, 1996)
The peak of the last glaciation (18,000 years BP) was evidenced by dry climatic condition and a narrow palaeoriver system in the Bengal basin. At the end of the last glaciation (about 10,000 years BP), amplified monsoon water plus deglaciated melt water from the Himalayas enormously flowed through these palaeoriver systems. The rivers were overloaded and overflowed, deposited a series of gravel beds in north Bengal, and also caused the erosion of Madhupur, Barind and Chalanbil, leaving a north-south elongated landmass. Sea-level started rising, attained its maximum height at about 5,500 years BP. The lines drawn from Ganakghata to North Nalbila in the Maiskhali Island and also from Cox's Bazar to Teknaf (eastern extremities of salt marshes) represent such an elevated palaeobeach line. Holocene sea level rise changed the hydrodynamic condition of river system and the deeply incised valleys were filled up with unconsolidated sediments. Holocene sea-level drop resulted the aerial exposition of the Hatia, Kutubdia, Sandip and other near shore islands of the Bay of Bengal.